Radar design principles : signal processing and the environment - Nathanson, Fred E. (SciTech Pub., 1999)
Offers coverage of digital technology, weather radar, microburst detection, and digital correlators. Provides an evaluation of theory as well as a review of development in practical equipment design and construction. Includes four chapters on equations and detection theory, plus seven on waveforms and signal processing.